Stretchable, Transparent, and Ultra-Broadband Terahertz Shielding Thin Films Based on Wrinkled MXene Architectures - Yang, Shaodian; Lin, Zhiqiang; Wang, Ximiao; Huang, Junhua; Yang, Rongliang; Chen, Zibo; Jia, Yi; Zeng, Zhiping; Cao, Zhaolong; Zhu, Hongjia; Hu, Yougen; Li, Enen; et al. (Nano-Micro Letters, 2024)
With the increasing demand for terahertz (THz) technology in security inspection, medical imaging, and flexible electronics, there is a significant need for stretchable and transparent THz electromagnetic interference (EMI) shielding materials. Existing EMI shielding materials, like opaque metals and carbon-based films, face challenges in achieving both high transparency and high shielding efficiency (SE). Here, a wrinkled structure strategy was proposed to construct ultra-thin, stretchable, and transparent terahertz shielding MXene films, which possesses both isotropous wrinkles (height about 50 nm) and periodic wrinkles (height about 500 nm). Compared to flat film, the wrinkled MXene film (8 nm) demonstrates a remarkable 36.5% increase in SE within the THz band. The wrinkled MXene film exhibits an EMI SE of 21.1 dB at the thickness of 100 nm, and an average EMI SE/t of 700 dB μm−1 over the 0.1–10 THz. Theoretical calculations suggest that the wrinkled structure enhances the film's conductivity and surface plasmon resonances, resulting in an improved THz wave absorption. Additionally, the wrinkled structure enhances the MXene films' stretchability and stability. After bending and stretching (at 30% strain) cycles, the average THz transmittance of the wrinkled film is only 0.5% and 2.4%, respectively. The outstanding performances of the wrinkled MXene film make it a promising THz electromagnetic shielding materials for future smart windows and wearable electronics. Highlights: 1 A stretchable, transparent, and ultra-broadband (0.1–10 THz) terahertz shielding MXene (Ti3C2Tx) film has been fabricated by a structure engineering strategy. 2 Theoretical calculations indicate that the wrinkled structure enhances the film's conductivity and surface plasmon resonances, resulting in an improved THz wave absorption. 3 The wrinkled MXene films exhibit superb conformability to surfaces with random curvatures, and can be used as a shielding film for THz imaging.